PERANAN PENYIDIK PEGAWAI NEGERI SIPIL BALAI BESAR PENGAWASAN OBAT DAN MAKANAN TERHADAP PEREDARAN KOSMETIK ILEGAL DIWILAYAH HUKUM KOTA PEKANBARU - Nadia Maharani; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Cosmetics today is already a requirement for women and men to beautify the appearance. Illegal cosmetics contain ingredients harmful to public health at the moment is a serious problem, because the cosmetic products containing hazardous substances are illegal and are still circulating freely in the market. The Center for Food and Drug Administration (BBPOM) is an institution that is given the task by the government to monitor the circulating the said cosmetic products illegal. The purpose of this thesis, namely; First, the role of civil servant investigators (investigators) BBPOM the offenses circulation of illegal cosmetics in Jurisdiction Pekanbaru, Second, obstacles PPNS BBPOM the offenses circulation of illegal cosmetics in Jurisdiction Pekanbaru, Third, efforts made PPNS BBPOM of the offenses the circulation of illegal cosmetics Jurisdiction in Pekanbaru.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on a study in order to provide a complete and clear picture of the issues examined. This research was conducted in BBPOM Pekanbaru, while the sample population is the whole party with regard to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study by observation, interview and literature study.From the research there are three main things that can be inferred. First, the role of investigators BBPOM Pekanbaru in solving cases of illegal cosmetic circulation is not optimal because there are many cases of illegal cosmetic circulation in Pekanbaru city, and a little more perpetrators are brought into the realm of law only administrative sanctions so the lack of deterrent effect on perpetrators. Second, obstacles PPNS BBPOM Pekanbaru in criminal cases the circulation of illegal cosmetics is, a lack of investigators, lack of coordination with the National Police, the factors of infrastructure, lack of public knowledge, perpetrators fled before the enactment as suspects, Third, efforts made PPNS BBPOM the case the crime of illegal cosmetics circulation is to conduct spot checks in coordination with the National Police to store cosmetics, kepasar-market, traditional markets, salons, and place of the alleged occurrence of illegal cosmetic storage, an investigation into the distributor. and BBPOM also do counseling and issued a public warning about cosmetics prohibited. Advice writer, first, it is expected that investigators BBPOM more leverage in dealing with the crime of trafficking illegal cosmetics in Pekanbaru so that the reduced circulation of illegal cosmetics stretcher community, Second, coordination PPNS BBPOM with police, traders and the public in dealing with the crime of trafficking illegal cosmetics in Pekanbaru, third, civil servants investigator large hall plus drug and food control to be optimized in the line of duty.Key: Part – PPNS – BBPOM – Ilegal Cosmetics